Changes in histidine metabolism through smoltification and effect on cataract development in Atlantic Salmon (Salmo salar L.) - Slaatmo, Oscar André (The University of Bergen, 2022)
Cataract is the collective definition of any light scattering opacities of the eye. Cataractogenesis is caused when there is a noticeable irregular light scattering because there has been a change in the tridimensional structure of the crystalline. This can be caused by two varieties of cataract, one irreversible, and one reversible osmotic form. The last type only happens when salmon move from freshwater to saltwater. Cataract investigations during the 90`s and early 2000`s revealed high prevalence and an increasing severity. The most believed reason for the major increase was the removal of bloodmeal from the feed, the second was the transition from fish oil to plant oil. As of 1995 it turned into one of the most economically important diseases in farmed salmon. This pushed research to find an understanding for the high prevalence of cataract and how to prevent it. The main purpose of this study was to investigate the interaction effect of histidine supplementation and dietary lipid in freshwater. Concentrations of NAH, histidine and histidine derivatives in heart, lens and muscle were decided through HPLC and ninhydrin detection. For three samplings fish were scored for cataract using the scale 0-4 developed by Wall and Bjerkås (1999). Findings in previous research have discovered histidine supplementation to have a preventative effect on cataract development. Histidine and histidine derivatives have important functions in the eye metabolism and osmotic function. The replacement of fish oil with a RAFOA mix (vegetable oil) has not previously shown to have any effect on cataract development. The findings in the present study support previous findings that histidine supplementation prevents cataract, but this study does show that vegetable oil has a negative effect on cataract development in freshwater. Masteroppgave i fiskehelse FISK399 MAMN-FISK